Gender difference in the prognostic value of estimated glomerular filtration rate at admission in ST-segment elevation myocardial infarction: a prospective cohort study. Issue 2 (2nd March 2012) - Damman, Peter; Kikkert, Wouter J; Woudstra, Pier; Kuijt, Wichert J; Grundeken, Maik J D; Harskamp, Ralf E; Baan, Jan; Vis, Marije M; Henriques, Jose P S; Piek, Jan J; van Straalen, Jan P; Fischer, Johan C; et al.
Abstract : Objective: To evaluate gender differences in the prognostic value of renal function for mortality in ST-segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PPCI). Design: Prospective single-center cohort. Setting: Single tertiary referral center in Amsterdam, The Netherlands. Patients consecutive STEMI patients undergoing PPCI (1412 men and 558 women). Main outcome measure: The authors calculated adjusted HRs for 3-year all-cause mortality according to the presence of a reduced renal function (estimated glomerular filtration rate <60 ml/min) using Cox proportional hazards models. In order to investigate a possible gender difference in the prognostic value of a reduced renal function, a comparison was made between the HRs of male and female patients and an interaction term was added to the model and tested for significance. Adjustments were made for age, body mass index, history of diabetes or hypertension, systolic blood pressure and heart rate, anterior myocardial infarction and time to treatment. Results: In male patients, a reduced renal function was associated with increased 3-year mortality (adjusted HR 6.31, 95% CI 3.74 to 10.63, p<0.001). A reduced renal function was associated with a twofold increase in the mortality hazard in female patients (adjusted HR 2.22, 95% CI 1.25 to 3.94, p=0.006). Conclusions: In this large single-centre registry of STEMI patients undergoing PPCI, renal dysfunction as assessed by estimated glomerular filtration rate had prognostic significance for mortality in both male and female patients.